(untitled) (Collection of scientific works «Modern structures of metal and wood», 2022)
The article presents the results of tests of concrete beams with basalt—plastic reinforcement (BFRP). These beams in previous studies were brought to the limit (ULS) state, and then reinforced with carbon fiber webs (CFRP). The established character of deformation, crack development and fracture used in beams with large (a/d=3) and medium (a/d=2) shear spans corresponded to the stress — strain state of almost balanced normal cross section. It was characterized by the achievement in the outer carbon—plastic layer of the strengthening of ultimate deformations and tensile stresses, and in the compressed zone of concrete — closed (in the descending section of the diagram " σ с —ε с ") stresses and strains. The destruction of beams with small (a/d=1) landslides was accompanied by further opening of previously formed inclined cracks and rupture of closed carbon fiber shirts on the side faces. Reinforcement of normal sections is recommended to be designed for cases of achievement of characteristic stresses in the stretched rod reinforcement with the subsequent rupture of external FAP—FRP reinforcement without destruction of the compressed zone of concrete. The resulting transverse force in the inclined section of the beam consists of the transverse forces perceived by the concrete of the compressed zone above the top of the dangerous inclined crack, composite reinforcement crossed by the crack, clamps or canvas with FAP—FRP. The method of determining the load—bearing capacity of inclined sections of unreinforced concrete beams reinforced with NCA—FRP is described in previously published works of the authors. The bearing capacity of the ULS—supported support sections of beam structures reinforced with FAP—FRP materials should be determined, first of all, by the action of the bending moment on the critical inclined crack.